Long-Term Effect of Weight Regain Following Behavioral Weight Management Programs on Cardiometabolic Disease Incidence and Risk: Systematic Review and Meta-Analysis. Issue 4 (28th March 2023) - Hartmann-Boyce, Jamie; Theodoulou, Annika; Oke, Jason L.; Butler, Ailsa R.; Bastounis, Anastasios; Dunnigan, Anna; Byadya, Rimu; Cobiac, Linda J.; Scarborough, Peter; Hobbs, F.D. Richard; Sniehotta, Falko F.; Jebb, Susan A.; et al.
Abstract : Background: Behavioral weight management programs (BWMPs) enhance weight loss in the short term, but longer term cardiometabolic effects are uncertain as weight is commonly regained. We assessed the impact of weight regain after BWMPs on cardiovascular risk factors, diabetes, and cardiovascular disease. Methods: Trial registries, 11 databases, and forward-citation searching (latest search, December 19) were used to identify articles published in English, from any geographical region. Randomized trials of BWMPs in adults with overweight/obesity reporting cardiometabolic outcomes at ≥12 months at and after program end were included. Differences between more intensive interventions and comparator groups were synthesized using mixed-effects, meta-regression, and time-to-event models to assess the impact of weight regain on cardiovascular disease incidence and risk. Results: One hundred twenty-four trials reporting on ≥1 cardiometabolic outcomes with a median follow-up of 28 (range, 11–360) months after program end were included. Median baseline participant body mass index was 33 kg/m 2 ; median age was 51 years. Eight and 15 study arms (7889 and 4202 participants, respectively) examined the incidence of cardiovascular disease and type 2 diabetes, respectively, with imprecise evidence of a lower incidence for at least 5 years. Weight regain in BWMPs relative to comparators reduced these differences. One and 5 years after program end, total cholesterol/HDL (high-density lipoprotein) ratio was 1.5 points lower at both times (82 studies; 19 003 participants), systolic blood pressure was 1.5 mm mercury and 0.4 mm lower (84 studies; 30 836 participants), and HbA1c (%) 0.38 lower at both times (94 studies; 28 083 participants). Of the included studies, 22% were judged at high risk of bias; removing these did not meaningfully change results. Conclusions: Despite weight regain, BWMPs reduce cardiometabolic risk factors with effects lasting at least 5 years after program end and dwindling with weight regain. Evidence that they reduce the incidence of cardiovascular disease or diabetes is less certain. Few studies followed participants for ≥5 years. Registration: URL: https://www.crd.york.ac.uk/PROSPERO/ ; Unique identifier: CRD42018105744.